2014
DOI: 10.1074/jbc.m113.516492
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear Aggregation of Mutant FUS/TLS as a Molecular Pathomechanism of Amyotrophic Lateral Sclerosis

Abstract: Background: Abnormal accumulation of mutant FUS/TLS is a pathological change in patients with amyotrophic lateral sclerosis (ALS). Results: A pathogenic mutation, G156E, increases propensities of FUS/TLS for aggregation in vitro and in vivo. Conclusion: Intranuclear aggregation of mutant FUS/TLS is a molecular pathomechanism of ALS. Significance: A loss of functional TLS/FUS in the nucleus will lead to neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
95
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 48 publications
5
95
1
1
Order By: Relevance
“…In contrast, our group has shown that a fulllength FUS protein dual-tagged with an N-terminal GST and a C-terminal 6x His remained soluble and we also found that an ALS-causing mutation, G156E, triggered the formation of insoluble aggregates with amyloid-like fibrillar morphologies (Nomura et al 2013). Furthermore, the fibrils of GST-FUS(G156E)-His reacted with Thioflavin T, suggesting distinct properties from those of the hydrogels prepared from the LC domain as mentioned above.…”
contrasting
confidence: 69%
See 3 more Smart Citations
“…In contrast, our group has shown that a fulllength FUS protein dual-tagged with an N-terminal GST and a C-terminal 6x His remained soluble and we also found that an ALS-causing mutation, G156E, triggered the formation of insoluble aggregates with amyloid-like fibrillar morphologies (Nomura et al 2013). Furthermore, the fibrils of GST-FUS(G156E)-His reacted with Thioflavin T, suggesting distinct properties from those of the hydrogels prepared from the LC domain as mentioned above.…”
contrasting
confidence: 69%
“…In many of aggregation-prone proteins, fusion with glutathione-S-transferase (GST) can increase their solubility; indeed, soluble FUS proteins can be prepared when tagged with an N-terminal but not C-terminal GST (Sun et al 2011). As shown by our group, however, most fractions of GST-FUS expressed in E. coli were collected as insoluble inclusions, and significant amounts of the truncated GST-FUS were also contaminated even after the affinity purification using glutathione Sepharose resins (Nomura et al 2013). We thus further attached a 6x His tag at the C-terminus of GST-FUS and then successfully removed the truncated proteins by additional purification using Ni 2+ -affinity resins.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The prion-like domain consists of an intrinsically disordered QGSY (glutamine-glycine-serine-tyrosine)-rich region (amino acids 1-164) and a glycine-rich region (amino acids 165-239). A missense mutation (G156E) in the QGSY-rich region has been found in patients with familial ALS and has been reported to cause intranuclear aggregation of FUS (17). However, the role of the QGSY-rich region in maintaining FUS intranuclear distribution and function under physiological conditions is unknown.…”
mentioning
confidence: 99%